Representation of Body Orientation in Vestibular-Defective Patients Before and After Unilateral Vestibular Loss - Borel, Liliane; Honoré, Jacques; Bachelard-Serra, Mathilde; Lavieille, Jean-Pierre; Saj, Arnaud (Frontiers in Systems Neuroscience, 2021)
Introduction: The unilateral vestibular syndrome results in postural, oculomotor, perceptive, and cognitive symptoms. The present study was designed to investigate the role of vestibular signals in body orientation representation, which remains poorly considered in vestibular patients. Methods: The subjective straight ahead (SSA) was investigated using a method disentangling translation and rotation components of error. Participants were required to align a rod with their body midline in the horizontal plane. Patients with right (RVN; n =8) or left vestibular neurotomy or vestibular schwannoma resection (LVN; n=13) were compared with 12 healthy controls. Patients were tested the day before surgery and during the recovery period, 7 days and 2 months after the surgery. Results: Before and after unilateral vestibular neurotomy, i.e., in the chronic phases, patients showed a rightward translation bias of their SSA, without rotation bias, whatever the side of the vestibular loss. The data show that the lower the translation error before neurotomy, the greater its increase two months after the total neurotomy, which led to a rightward translation of similar amplitude in the two groups of patients. In the early phase after surgery, SSA moved toward the operated side both in translation and in rotation, as typically found for biases occurring after unilateral vestibular loss, such as the subjective visual vertical bias (SVV). Discussion-Conclusion: This work gives the first description of the immediate consequences and of the recovery time-course of body orientation representation after a complete unilateral vestibular loss. The overall evolution differed according to the side of the lesion with more extensive changes over time after left vestibular loss. It is noteworthy that representational disturbances of self-orientation were highly unusual in the chronic stage after vestibular loss and similar to those reported after hemispheric lesions causing spatial neglect, while classical ipsilesional biases were reported in the acute stage. This study strongly supports the notion that the vestibular system plays a major role in body representations processes and more broadly on spatial cognition. From a clinical point of view, SSA appeared to be a reliable indicator for the presence of a vestibular disorder.